2010
DOI: 10.1021/mp100280b
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Ultrasound Enhances Nanoparticle Penetration into Breast Cancer Spheroids

Abstract: Effective treatment of solid tumors requires homogenous distribution of anticancer drugs within the entire tumor volume to deliver lethal concentrations to resistant cancer cells and tumorinitiating cancer stem cells. However, penetration of small molecular weight chemotherapeutic agents and drug-loaded polymeric and lipid particles into the hypoxic and necrotic regions of solid tumors remains a significant challenge. This article reports the results of pulsed ultrasound enhanced penetration of nano-sized fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 78 publications
2
61
0
1
Order By: Relevance
“…MCF-7 breast cancer spheroids were treated with nanosized fluorescent particles with and without the application of pulsed ultrasound. It was found that the particles achieved sixfold to 20-fold higher penetration with the application of ultrasound [76]. In this study, the penetration was also found to be size and charge dependent.…”
Section: Use Of Spheroids For Accelerated Testingsupporting
confidence: 55%
“…MCF-7 breast cancer spheroids were treated with nanosized fluorescent particles with and without the application of pulsed ultrasound. It was found that the particles achieved sixfold to 20-fold higher penetration with the application of ultrasound [76]. In this study, the penetration was also found to be size and charge dependent.…”
Section: Use Of Spheroids For Accelerated Testingsupporting
confidence: 55%
“…Since multicellular spheroids (MCs) represent more closely the heterogeneity of the tumour microenvironment with a hypoxic core and normoxic surface 32,33 compared with traditional monolayer cell cultures, we incubated SH-SY5Y MCs with Ir-PVP. The strong phosphorescence signal of Ir-PVP was observed in the core of spheroids, while almost no signal was detected on the surface of spheroids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The conjugate was ten-fold more selective for HER2-positive cells compared with soluble pyropheophorbide-a. Vrouenraets et al 95 directly used mAbs against tumor-associated antigens for the targeting of photosensitizers to improve the selectivity of PDT and found that AlPc(SO 3 H) 4 showed promising potential for use in PDT when coupled to internalizing tumor-selective mAbs.…”
Section: Antibody-based Targetingmentioning
confidence: 99%